The Participatory Art Museum: Approached from a Philosophical Perspective. (14th October 2016) - Hegenbart, Sarah
Abstract: This chapter introduces the participatory art museum and discusses some of the challenges it raises for philosophical aesthetics. Although participatory art is now an essential part of museological programming, an aesthetic account of participatory art is still missing. The chapter argues that much could be gained from exploring participatory art, as it raises fundamental challenges to our understanding of issues in aesthetics, such as the nature of aesthetic experience, the value of art, and the role of the spectator. Moreover, participatory art fundamentally questions the status of the museum as an exhibition space for contemporary art practices.